2020
DOI: 10.3389/fonc.2020.00013
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Modeling Metastasis Biology to Improve Therapeutic Strategies for Combating Osteosarcoma Progression

Abstract: Osteosarcoma is a malignant primary tumor of bone, arising from transformed progenitor cells with osteoblastic differentiation and osteoid production. While categorized as a rare tumor, most patients diagnosed with osteosarcoma are adolescents in their second decade of life and underscores the potential for life changing consequences in this vulnerable population. In the setting of localized disease, conventional treatment for osteosarcoma affords a cure rate approaching 70%; however, survival for patients suf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
70
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 269 publications
(287 reference statements)
0
70
0
Order By: Relevance
“…In humans, the disease most commonly affects adolescents, while middle-to-older aged canines are impacted [ 42 , 43 , 44 ]. Histologically, OSA is characterised by transformed bone progenitor cells that produce immature osteoid, while radiographically, it presents as a ‘sunburst’ appearance or triangular appearance (‘Codman’s Triangle’) due to the osteolytic or osteoblastic nature, and the bone lesion’s ability to elevate the periosteal surface, respectively [ 45 , 46 ]. The disease most commonly presents in the metaphyseal region of long bones of the limb such as the femur, tibia or humerus [ 47 ].…”
Section: Osteosarcomamentioning
confidence: 99%
“…In humans, the disease most commonly affects adolescents, while middle-to-older aged canines are impacted [ 42 , 43 , 44 ]. Histologically, OSA is characterised by transformed bone progenitor cells that produce immature osteoid, while radiographically, it presents as a ‘sunburst’ appearance or triangular appearance (‘Codman’s Triangle’) due to the osteolytic or osteoblastic nature, and the bone lesion’s ability to elevate the periosteal surface, respectively [ 45 , 46 ]. The disease most commonly presents in the metaphyseal region of long bones of the limb such as the femur, tibia or humerus [ 47 ].…”
Section: Osteosarcomamentioning
confidence: 99%
“…Unfortunately, clinical studies, such as those examining targeted agents, have shown disappointing results and changed little in the last three decades [1] . For the development of novel treatments to improve the prognosis of osteosarcoma patients, further elucidation of the molecular mechanisms that support the invasion and proliferation of osteosarcoma cells is of paramount importance [6] , [7] , [8] , [9] , [10] .…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common primary bone tumor and is highly malignant [ 1 ]. Neoadjuvant and adjuvant chemotherapy for osteosarcoma has largely remained unchanged since the 1980s, with wide surgical excision and preservation of limb function [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Osteosarcoma is the most common primary bone tumor and is highly malignant [ 1 ]. Neoadjuvant and adjuvant chemotherapy for osteosarcoma has largely remained unchanged since the 1980s, with wide surgical excision and preservation of limb function [ 1 ]. However, despite such treatment, only 60–70% of patients without clinically evident metastasis at first diagnosis remain alive after 3 years [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation